Comparison of Clinical Outcomes of Diabetes Mellitus Patients with COVID-19 Confirmed Diabetes Mellitus Patients at One of the Hospital Bantul - Nadliroh, Lubabun; Estiningsih, Daru; Sarwadhamana, Raden Jaka; Ninisita Sri Hadi (Jurnal Kefarmasian Indonesia, 2024)
SARS-CoV-2-infected patients with comorbid DM are very likely to experience a significant reduction in glycemic control and eventually require adjustment of antidiabetic treatment to optimize clinical outcomes. The results of data collected by the COVID-19 Handling Task Force, the total number of cases in Indonesia that were confirmed positive for COVID-19 had comorbidities, one of which was Diabetes Mellitus 33.6%. This study aimed to determine whether or not there were differences in clinical outcomes of DM patients with confirmed COVID-19 and DM without confirmed COVID-19 at One of Hospital Bantul. This type of research is observational with a cross-sectional design. Secondary data in the form of medical records. Sampling was carried out using a simple random sampling method with the Lemeshow formula. The data were analyzed using the Mann-Whitney test in bivariate analysis. The results showed that the clinical outcome of type 2 DM patients with confirmed COVID-19 was the GDS target value (38.9%) and the GDS target value (61.1%). The clinical outcome of patients with type 2 diabetes who did not have confirmed COVID-19 was that the GDS target value (55.6%) was achieved and the GDS target value was not reached (44.4%). The results of the Mann-Whitney test showed a significant difference in clinical outcome p=0.046 between DM type 2 confirmed COVID-19 and DM type 2 not confirmed COVID-19. It can be concluded that DM patients with confirmed COVID-19 have different clinical outcomes than DM patients without confirmed COVID-19.